A Novel Study of Synthesis and Experimental Investigation on Hybrid Biocomposites for Biomedical Orthopedic Application. (28th November 2021) - Rao, C. V. Subba; Sabitha, R.; Murugan, P.; Rao, S. Rama; Anitha, K.; Rao, Y. Sesha
Abstract : In recent years the biocomposites are highly utilized in the biomedical applications, due to excellent strength as well as weight ratio. A lot of natural fibers, namely, flax, hemp, jute, kenaf, and sisal are cheaply available in colossal amount. Aim of this study, a novel approach, is executed for construction of biomedical orthopedic parts by using mixture of natural fibers. This work handled biocomposites such as flax fiber (FX), chicken feather fiber (CF), kenaf fiber (KF), and rice husk fiber (RH) effectively. From all these composites, four sets of mixed fibers with reinforcement of polylactic acid polymer used for creating orthopedic parts. The hand-lay-based methodology is undertaken for preparation of hybrid biocomposites. Parameters involved for this study are fiber types (KF + RH, RH + FX, FX + CF, and CF + KF), laminate count (2, 4, 6 and 8) infill density (30%, 60%, 90%, and 120%), and raster angle (0/60, 30/120, 50/140, and 70/160). Finding of this work is dimensional accuracy, flexural strength, and shore hardness that are analyzed by L16 orthogonal array. ANOVA statistical analysis is enhanced and enlightens the results of flexural strength and source hardness of the biocomposites. Amongst in four parameters, the fiber type parameter extremely contributes such as 40.50% in the flexural analysis. Similarly, laminate count parameter highly contributes such as 31.01% in the shore hardness analysis.